Does the long-term contamination of lead (PbII) affect the bioremediation mechanisms of Microbacterium oxydans strain CM3 and CM7?. Issue 8 (17th November 2022) - Ashrafi, Zahra; Heidari, Parviz; Mojerlou, Shideh
ABSTRACT: Lead (Pb(II)) is a heavy metal with harmful effects on ecosystems and living organisms. Bacteria are used as part of the microorganisms involved in Pb(II) bioremediation. Herein, the effects of long-term (20 months) Pb(II) contamination (LTC) under a continuous sub-culturing system were evaluated on the growth rate, Pb-remediation potential, and Pb-remediation mechanisms of two strains, CM3 and CM7, of Microbacterium oxydans . LTC affected the optimal pH and temperature, and increased the growth rate of bacterial strains in the Pb(II) environment compared with native strains. Besides, the Pb-remediation potential of strains from LTC, CM3-b, and CM7-b, was significantly increased at pH 6.5. The biomass of strains was analyzed in terms of topographical and elemental percentage using SEM. LTC did not change the cell shape and dimensions of the studied strains. The Pb(II) percentage was significantly increased in sediments of the bacterial strains from LTC grown at pH 6.5, while the Pb(II) percentage was significantly reduced in the cell surface of strains grown under the LTC system. A correlation was found between P and Pb(II) percentage in the biomass of strains from LTC, indicating that these strains further precipitated Pb(II) in the form of lead phosphate. Furthermore, LTC reduced Pb(II) accumulation into the cell wall of strains.